Manajemen Perencanaan Pembelajaran Berbasis Kolaboratif dalam Peningkatan Kompetensi Pedagogik Guru di SD Negeri Batujaya - Cacang Cacang; Mohamad Ramdhan; Atam Supatma; Ramdani Sutrisna; Halimatussadiah Halimatussadiah; Dinny Mardiana (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Learning planning is a strategic component of instructional management because it guides teachers in linking objectives, materials, learning strategies, media, and assessment with students' characteristics. In practice, however, learning plans are often prepared individually and tend to be administrative, so teachers have limited opportunities to reflect on pedagogical decisions with colleagues. This study aims to describe and analyze collaborative-based learning planning management in improving teachers' pedagogical competence at SD Negeri Batujaya. The study used a descriptive qualitative approach with a case study strategy. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The field data show that SD Negeri Batujaya has nine educators and education personnel consisting of one principal, six classroom teachers, and two subject teachers. The school also holds a teacher learning community twice a month. The findings indicate that collaborative planning is supported by the principal's academic leadership, the small number of teachers that enables intensive coordination, and the existence of a routine learning community. Collaboration helps teachers discuss teaching modules, student characteristics, learning strategies, media, and assessment. The main constraints are limited time, unequal teacher participation, and limited learning facilities. The study implies that a structured learning community can serve as a practical managerial strategy for strengthening teachers' pedagogical competence in elementary schools.